An ultra-thick polydopamine-modified Dx-PAN@PDA@Ag core-shell photothermal fiber membrane and its preparation method and application

By using ultra-thick polydopamine layer and silver nanoparticles in the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane, the problems of low thermal utilization capacity and uneven load of existing photothermal materials are solved, and efficient photothermal seawater desalination and stable fiber membrane performance are achieved.

CN116770588BActive Publication Date: 2025-03-28SHANDONG JIANZHU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310725966.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-03-28
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

The existing photothermal materials have low heat utilization capacity in the aqueous phase, resulting in low solar heat conversion efficiency. As the photothermal material, polydopamine has problems such as insufficient single load capacity and uneven loading inside and outside the material.

Method used

The Dx-PAN@PDA@Ag core-shell photothermal fiber membrane modified with an ultra-thick polydopamine layer was prepared by electrospinning technology, and loaded with silver nanoparticles to form a fiber membrane with high photothermal properties.

Benefits of technology

It realizes efficient rapid desalination of photothermal seawater, the ultra-thick polydopamine shell of the fiber membrane improves the photothermal ability and mechanical properties, and the silver nanoparticles enhance the light absorption rate, avoid salt accumulation, and ensure the stability of long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0004292799250000011
    Figure HDA0004292799250000011
  • Figure HDA0004292799250000012
    Figure HDA0004292799250000012
Patent Text Reader

Abstract

The present invention belongs to the field of energy and chemical industry, and specifically relates to an ultra-thick polydopamine-modified Dx-PAN@PDA@Ag core-shell photothermal fiber membrane and its preparation method and application. The Dx-PAN@PDA@Ag core-shell photothermal fiber membrane provided by the present invention is composed of a polyacrylonitrile-dopamine fiber membrane and an ultra-thick polydopamine shell layer; the loading amount of silver nanoparticles is 1%-20%. The present invention prepares a Dx-PAN@PDA@Ag nanofiber membrane with an ultra-thick photothermal polydopamine shell layer, and the ultra-thick PDA shell layer provides a super-hydrophilic fiber surface and a strong photothermal capacity. The discontinuous cavities inside photothermal materials such as aerogels and foams are easily dissolved in accumulated water and at the same time hinder the overflow of water vapor. However, there is no accumulation of water on the surface of the super-hydrophilic fiber, so that the heating process only heats a thin layer of water on the surface of the photothermal fiber membrane. When the photothermal fiber membrane of the present invention is used for seawater desalination, the equipment is simple, the manual operation is less, and the photothermal conversion capacity is strong.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy and chemical industry, and specifically relates to an ultra-thick polydopamine-modified Dx-PAN@PDA@Ag core-shell photothermal fiber membrane and a preparation method and application thereof. Background Art

[0002] In recent years, unprecedented fossil fuel consumption has caused serious environmental problems. It is absolutely critical to explore clean, renewable and sustainable energy and technological options to reduce dependence on fossil fuels. Solar energy is considered to be an environmentally friendly and inexhaustible energy source. There are two main strategies for the economicization of solar energy: photovoltaic conversion and photothermal conversion. Among them, the main application of photothermal conversion is to use photothermal conversion materials to obtain solar energy and evaporate water to ensure the desalination and purification of seawater to obtain clean water to meet the drinking water needs of people in coastal areas where fresh water is scarce. The main operating units of photothermal seawater desalination include membrane separation and thermal distillation. However, due to the low heat utilization capacity of the traditional thermal distillation process in the water phase, it causes unsatisfactory energy waste and there is a problem of low solar thermal conversion efficiency.

[0003] Photothermal materials can be used for the effective collection of solar energy. The selection of excellent photothermal materials is a key step in achieving efficient water evaporation. Photothermal materials include carbon-based materials, metal plasma materials and semiconductor materials. Carbon-based materials are easy to prepare, corrosion-resistant, and stable, which are more suitable for water evaporation and meet the key requirements of support and capillary water transport. Polydopamine is a synthetic analog of natural melanin. It not only contains functional groups such as catechol, amine and imine on the surface, but also inspired by mussel foot protein. PDA has been easily attached to almost all types of substrates, even those with low surface energy. Due to the diversity of PDA chemical functional groups, the hydrophilicity of the substrate can be effectively improved. At the same time, polydopamine, as a photothermal conversion material, has been widely used in photothermal cancer therapy, solar distillation and other aspects in recent years. Our research group previously combined high specific surface area electrospun fibers with the photothermal properties of polydopamine, externally loaded MOF catalysts, and greatly improved the catalyst activity by using the photothermal properties of polydopamine. Therefore, polydopamine as a photothermal-assisted catalysis is a very feasible and general strategy that does not require high requirements on the surface properties of the catalyst.

[0004] In recent years, plasmonic nanoparticles have the ability of photothermal heating due to their local surface plasmon resonance effect, which can absorb light energy and convert it into heat energy. Recently, gold nanoparticles heated by solar photothermal heating have been applied to evaporate water for seawater desalination and purification. People fix gold nanoparticles in porous support materials such as cellulose paper, dust-free paper, polymer nanofiber membranes and nanoporous alumina to avoid the agglomeration effect of the material. When the porous material anchored by gold nanoparticles floats on the water surface, the heat energy generated by the gold nanoparticles selectively heats the water surface after being irradiated by sunlight on the surface, thereby increasing the evaporation rate of water by suppressing heat loss. However, the expensiveness of gold nanoparticles still requires alternative effective materials, and at the same time seeks in-situ growth methods to replace chemical bonds and to consolidate the stability of plasmonic materials.

[0005] The reducibility of polydopamine provides a new option for the in-situ synthesis and loading of plasma photothermal materials. However, polydopamine as a photothermal material still has some problems. For example, most of the literature reported so far is that dopamine self-polymerizes on the surface of the material to form a thinner polydopamine. Due to the insufficient single loading amount, multiple continuous loadings are required to achieve a certain thickness. At the same time, there is a problem of uneven loading inside and outside the material. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention has developed a Dx-PAN@PDA@Ag core-shell photothermal fiber membrane modified with an ultra-thick polydopamine layer. The electrospun Dx-PAN@PDA@Ag core-shell photothermal fiber membrane based on the ultra-thick polydopamine layer can utilize clean and widespread solar energy to achieve rapid photothermal seawater desalination.

[0007] The present invention also provides a method for preparing the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane modified with the ultra-thick polydopamine layer.

[0008] Another object of the present invention is to provide an application of the above-mentioned ultra-thick polydopamine layer modified Dx-PAN@PDA@Ag core-shell photothermal fiber membrane in photothermal seawater desalination.

[0009] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0010] The present invention provides a Dx-PAN@PDA@Ag core-shell photothermal fiber membrane modified with an ultra-thick polydopamine layer. The fiber membrane is composed of a polyacrylonitrile-dopamine fiber membrane and an ultra-thick polydopamine shell layer. The dopamine content in the polyacrylonitrile-dopamine fiber membrane is 0.1-3.00 mg / cm 2; The fiber diameter of the polyacrylonitrile-dopamine fiber membrane is 80-100nm; the thickness of the polydopamine shell layer is 400-600nm; after the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane is loaded with silver nanoparticles, the particle size of the silver nanoparticles is 20-30nm, and the loading amount of the silver nanoparticles is 1%-20%.

[0011] The present invention also provides a method for preparing a Dx-PAN@PDA@Ag core-shell photothermal fiber membrane, comprising the following steps:

[0012] 1) Preparation of PAN-DA electrospinning solution: Dissolve DA in DMF, stir at room temperature, then add PAN, and continue stirring until all dissolved to obtain PAN-DA electrospinning solution, recorded as Dx-PAN spinning solution;

[0013] 2) Preparation of electrospun Dx-PAN nanofiber membrane: The PAN-DA electrospinning solution was loaded into a syringe for electrospinning; after the spinning was completed, the electrospun membrane was removed and naturally dried for later use, which was recorded as the Dx-PAN nanofiber membrane;

[0014] 3) Preparation of electrospun Dx-PAN@PDA core-shell photothermal fiber membrane with ultra-thick polydopamine layer: Take the prepared Dx-PAN nanofiber membrane, immerse it in Tris-HCl solution of DA, and stir it at room temperature; rinse the prepared membrane, vacuum dry it and set it aside, record it as Dx-PAN@PDA;

[0015] 4) Preparation of electrospun Dx-PAN@PDA@Ag core-shell photothermal fiber membrane with ultra-thick polydopamine layer: Take the prepared Dx-PAN@PDA nanofiber membrane, immerse it in AgNO3 solution, let it stand for a period of time, rinse it with ultrapure water, and vacuum dry it to obtain Dx-PAN@PDA@Ag core-shell photothermal fiber membrane.

[0016] Preferably, in step 1), the concentration of DA dissolved in DMF is 4-120 mg / mL; the stirring time is 1 h; the molecular weight of PAN is between 80,000 and 150,000; the mass ratio of DA to PAN is 1:10 to 1:1; in Dx-PAN, x is the content of DA, and the range of x is 0.1 g to 1.0 g.

[0017] Preferably, in step 2), the electrospinning parameters are: adjusting the distance between the electrospinning needle and the receiving device to 12-20 cm, the needle height to 35-45 cm, the injection speed to 0.01-0.1 mm / h, the voltage to 7-20 kV, the spinning needle moving distance to 20-100 cm, and the spinning time to 4-24 h.

[0018] Preferably, in step 3), the concentration of DA in the Tris-HCl solution is 0.05-5 mg / mL; the Tris-HCl solution is a 0.1-0.6 wt % aqueous solution of tris(hydroxymethyl)aminomethane, the hydrochloric acid concentration is 0.1 M, and the pH of the solution is adjusted to 8.5; the stirring time at room temperature is 24 h; and the vacuum drying time is 12 h.

[0019] Preferably, in step 4), the concentration of the AgNO3 solution is 1-100 mM; the standing time is 1-30 min; and the vacuum drying time is 12 h.

[0020] Preferably, the polyacrylonitrile includes but is not limited to nylon 6, PVDF, polyurethane and other polymers to construct similar structures.

[0021] The present invention also provides an application of the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane in photothermal desalination of seawater.

[0022] In the application test of the electrospun Dx-PAN@PDA@Ag core-shell photothermal fiber membrane based on the ultra-thick polydopamine layer provided by the present invention, the simulated seawater used was a 3.5% sodium chloride aqueous solution; the seawater desalination device was a personal device, including a sealed cabin, a simulated seawater cabin, a water-conducting cotton swab, a photothermal membrane, and a freshwater collection cabin; the light used was simulated sunlight with a light density of 1 kW / m 2 (1 simulated sunlight. Note it as 1-sun).

[0023] The application of the above fiber membrane comprises the following steps:

[0024] Steam generation experiment under different light densities: In order to evaluate the solar steam generation performance of the photothermal film, a 200 ml beaker filled with water was placed on an electronic balance with an accuracy of 0.001 g. Water was adsorbed 6 cm above the water surface by the capillary effect of a cotton swab, which was covered with the photothermal fiber membrane. At the same time, the membrane was covered on the cotton swab and sealed with polystyrene foam on all sides. The laboratory irradiation simulator (xenon lamp, Zhongjiao Jinyuan) was used for irradiation and the light intensity density was measured using a portable optical power meter. Steam generation experiments of Dx-PAN@PDA and Dx-PAN@PDA@Ag photothermal films were carried out under 1-sun, 3-sun, 5-sun, and 9-sun, respectively, and the amount of water evaporation was measured. As a control, the amount of water evaporation of Dx-PAN@PDA and Dx-PAN@PDA@Ag photothermal films under dark conditions was measured.

[0025] For the above application, the photothermal evaporation rate under 1-sun reached 1.91 kg m -2 h -1In the present invention, DA is dopamine hydrochloride with a purity of 98%; in the above step 1), x in the Dx-PAN spinning solution refers to the content of DA.

[0026] The present invention blends DA with PAN, and then utilizes the seed effect of the DA-PAN blended film to synthesize a single ultra-thick polydopamine-coated PAN fiber, and utilizes the reducing property of polydopamine to silver ions to obtain photothermal plasma silver nanoparticles by in-situ reduction. The prepared super-hydrophilic strong photothermal fiber membrane avoids the accumulation of water in the foam or aerogel cavity, realizes an ultra-thin water film on the surface of the material during the heating process, and can achieve rapid evaporation of the thin layer of water film under sunlight, with a high surface temperature. At the same time, the gaps between the fibers can provide an effective channel for desalination, avoiding the deposition of salt on the surface, and there is still no salt deposition after continuous use for half a month. In addition, the fiber membrane has good chemical stability and can be continuously and stably used for rapid desalination of photothermal seawater.

[0027] The beneficial effects of the technical solution of the present invention are:

[0028] (1) The present invention prepares a Dx-PAN@PDA@Ag nanofiber membrane with an ultra-thick photothermal polydopamine shell. The ultra-thick PDA shell provides a super-hydrophilic fiber surface and strong photothermal capacity. The discontinuous cavities inside photothermal materials such as aerogels and foams are easily dissolved in the accumulated water and hinder the escape of water vapor. However, there is no accumulated water on the surface of the super-hydrophilic fiber, so that the heating process only heats a thin layer of water on the surface of the photothermal fiber membrane.

[0029] (2) The gaps between the fibers of the fiber membrane provided by the present invention can support a small amount of thin water film, providing an effective channel for high-salinity to return to simulated seawater after evaporation, thereby preventing salt accumulation on the surface. Even if salt stains appear during long-term use, they will dissolve quickly.

[0030] (3) During the application of the present invention, the capillary effect of the cotton swab transfers water to the fiber membrane, and the water film is spread out by relying on the super-hydrophilic ability of the fiber membrane surface, so as to achieve the purpose of making the water film thin enough; the spatially separated evaporation device, the thinner fiber membrane is directly spread on the cotton swab with a relatively low thermal conductivity (~0.04W m-1 K-1), which can suppress the heat loss from the evaporation surface to the bulk water. It has the characteristics of being cheap, portable, and presenting an integrated design; the inherent capillary action of the cotton swab automatically absorbs seawater without the need for external power; it does not involve complex instrument operation, the reagents used are safe and non-toxic, the operation is simple, and it meets the conditions of daily household water use, and has good application prospects.

[0031] (4) When the photothermal fiber membrane of the present invention is used for seawater desalination, the equipment is simple, the human operation is less, and the photothermal conversion capacity is strong; and the required equipment is portable, suitable for areas with harsh conditions and lack of electricity, to provide fresh water for people's survival. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the preparation of photothermal fiber membrane and its application in seawater desalination;

[0033] Figure 2 Stability of (a) PAN, (b) PAN@PDA, and (c) D-PAN@PDA@Ag fiber membranes in acidic solutions.

[0034] Figure 3 Stability of (a) flexibility and (b) mechanical strength of wet D-PAN@PDA nanofibrous membrane in acidic solution; (c) Comparison of tensile stress-strain curves of dry / wet D-PAN@PDA nanofibrous membrane and conventional PAN fiber membrane;

[0035] Figure 4 (a) D-PAN nanofibers, (b / c) D-PAN@PDA nanofibers and enlarged SEM images of fiber cross sections, (d) SEM image of D-PAN@PDA@Ag nanofibers, (e) TEM image, (f) XRD image, (g) HAADF-STEM image, corresponding element surface distribution map (C, N, O and Ag) and line scan data map, (h) thermogravimetric analysis of D-PAN@PDA and D-PAN@PDA@Ag nanofibers;

[0036] Figure 5 (a) With water as the blank, the temperature of PAN, PAN@PDA, D-PAN@PDA, and D-PAN@PDA@Ag fiber membrane aqueous solutions changes with the extension of light exposure time; (b) Contact angle test of (i) D-PAN, (ii) D-PAN@PDA, and (iii) D-PAN@PDA@Ag fiber membranes; (c) Absorption intensity comparison of nanofiber membranes;

[0037] Figure 6 Digital photo of a large area of ​​D-PAN@PDA@Ag film (30cm*30cm) in a wet state;

[0038] Figure 7 Chemical structure of PDA molecule and molecular orbitals calculated using DFT theory at B3LYP / 6-31 G(d,p) level;

[0039] Figure 8(a) Water evaporation rate of cotton swab, PAN, PAN@PDA, PAN@PDA@Ag, D-PAN@PDA and D-PAN@PDA@Ag fiber membrane-based photothermal evaporators under 1-sun light irradiation; (b) Thermal infrared imaging of D-PAN@PDA@Ag fiber membrane-based photothermal evaporator under 1-sun light irradiation for 30 minutes and (c) Changes of water evaporation amount over time under 1-sun, 3-sun and 5-sun irradiation; (d) Stability test of water evaporation performance of D-PAN@PDA and D-PAN@PDA@Ag fiber membrane-based evaporators under 1-sun light irradiation; (e) Ion concentration of simulated seawater and clean water collected after evaporation by D-PAN@PDA@Ag nanofiber membrane evaporator; (f) Literature comparison of evaporation rate and energy conversion efficiency of PDA-type evaporators;

[0040] Fig. 9 Changes of water evaporation amount over time from D-PAN@PDA fiber membrane-based evaporator under 1-sun, 3-sun, and 5-sun illumination;

[0041] Fig.10 This is a D-PAN@PDA@Ag-NFM based seawater desalination device. DETAILED DESCRIPTION

[0042] The present invention is described in conjunction with specific embodiments. Various substitutions or changes made according to common technical knowledge and customary means in the art without departing from the above technical concept of the present invention are all included in the scope of the present invention.

[0043] Example 1

[0044] 1) Preparation of PAN-DA electrospinning solution: Dissolve DA in 10 mL DMF to a concentration of 50 mg / mL, stir at room temperature for 1 hour, then add 1 g PAN, and continue stirring until all PAN is dissolved to obtain PAN-DA electrospinning solution, which is referred to as Dx-PAN spinning solution, where x refers to the DA content;

[0045] 2) Preparation of electrospun Dx-PAN nanofiber membrane: PAN-DA electrospinning solution was loaded into a syringe, and the distance between the electrospinning needle and the receiving device was adjusted to 18 cm, the needle height was 43.5 cm, the injection speed was 0.05 mm / h, the voltage was 10 kV, the spinning needle moving distance was 30 cm, and the spinning time was 10 h. After the spinning was completed, the electrospun membrane was removed and dried naturally for later use, and recorded as Dx-PAN nanofiber membrane, such as Figure 1 As shown;

[0046] 3) Preparation of Dx-PAN@PDA core-shell photothermal fiber membrane by electrospinning with ultra-thick polydopamine layer: Take the prepared Dx-PAN nanofiber membrane, immerse it in Tris-HCl solution of DA, and stir it at room temperature for 24 hours. Rinse the prepared membrane with ultrapure water to remove excess DA solution, dry it in a vacuum oven and set it aside, recorded as Dx-PAN@PDA. In this work, a dense polymer PDA shell layer is formed on the surface of PAN nanofibers after induced in situ polymerization, and its mussel-like properties greatly improve the mechanical properties of the fiber membrane. Figure 3 As shown in a, in order to evaluate the flexibility and mechanical properties of the D-PAN@PDA membrane, the wet fiber membrane can be folded and unfolded multiple times without destroying the structure, and even folded into a complex shape. The fiber membrane will not be damaged after unfolding again, showing excellent flexibility. This easy folding and curling property makes the fiber membrane easy to store, transport and apply. Figure 3 b shows that the fiber membrane can easily lift a weight of 1.0 kg after being folded, indicating that the fiber membrane has not only good flexibility but also high strength. Next, we compared the stress-strain curves of PAN fiber membrane and PAN@PDA fiber membrane. Figure 3 As shown in Figure c, compared with pure PAN nanofiber membrane, the strength of PAN@PDA nanofiber membrane is significantly improved, and its breaking strength reaches 3.9 MPa, which is 3.6 times that of PAN nanofiber membrane. Especially when the fiber membrane is wetted with water, its mechanical properties are further improved, and the breaking strength (6.2 MPa) and elongation at break (23%) are 6.1 times and 1.5 times that of PAN fiber membrane, respectively.

[0047] 4) Preparation of Dx-PAN@PDA@Ag core-shell photothermal fiber membrane by electrospinning of ultra-thick polydopamine layer: Take the prepared Dx-PAN@PDA nanofiber membrane, immerse it in AgNO3 solution, let it stand for 1-30min, rinse it with ultrapure water, dry it in a vacuum oven and set it aside, recorded as Dx-PAN@PDA@Ag.

[0048] The fiber membrane prepared in Example 1 is composed of a polyacrylonitrile (PAN)-dopamine (DA) fiber membrane and an ultra-thick polydopamine (PDA) shell layer. The dopamine content in the polyacrylonitrile-dopamine fiber membrane is 0.1-3.00 mg / cm 2 ; The polyacrylonitrile-dopamine fiber membrane is white, with a fiber diameter of 80-100nm, polydopamine is a black opaque polymer, and the thickness of the polydopamine shell is about 200nm; after the electrospun core-shell photothermal fiber membrane based on the ultra-thick polydopamine layer is loaded with silver nanoparticles, the particle size of the silver particles is 20-30nm, and the loading amount of silver nanoparticles is 1%-20%. Figure 1The figure shows the schematic diagram of the preparation process of the fiber membrane. The scanning electron microscope photo of the nanofiber membrane clearly shows the formation of silver nanoparticles on the surface of the fiber membrane. Figure 4 In ac, the SEM and TEM images of D-PAN@PDA@Ag nanofiber membranes show that Ag nanoparticles are uniformly deposited on the fiber surface, and most of the particles are about 30 nm in diameter ( Figure 4 d / e). The XRD pattern of D-PAN@PDA@Ag nanofiber membrane shows a series of diffraction peaks at 38°, 44°, 64° and 77°, corresponding to the (111), (200), (220) and (311) crystal planes of face-centered cubic Ag nanoparticles ( Figure 4 f), demonstrating the formation of highly crystalline Ag single substance.

[0049] Example 2

[0050] Compare the stability of PAN, PAN@PDA, and Dx-PAN@PDA fiber membranes in 0.1M silver nitrate solution. 2 The PAN, PAN@PDA, and Dx-PAN@PDA fiber membranes were placed in 5 mL of 0.1 M silver nitrate aqueous solution, and the macroscopic morphological changes of the fiber membranes before and after placement were observed to determine the stability of the fiber membranes. Figure 3 a\b It can be seen that PAN and PAN@PDA cannot exist stably in acidic solution. PAN fiber membrane shrinks into a small ball immediately in acidic silver nitrate solution. Figure 2 c It can be seen that the PAN@PDA fiber membrane curls up to a certain extent in the acidic silver nitrate solution. Only the Dx-PAN@PDA fiber membrane with an ultra-thick polydopamine shell has no visible changes in the acidic silver nitrate aqueous solution.

[0051] Example 3

[0052] Investigate the flexibility and toughness of Dx-PAN@PDA@Ag nanofiber membrane: Figure 4 As shown in Figure d, the element distribution mapping photos and X-ray diffraction analysis diagrams of the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane loaded with silver nanoparticles confirm that silver nanoparticles are uniformly generated on the fiber surface. In order to more clearly analyze the preparation process of core-shell fibers, we used SEM, XRD, XPS and other methods to characterize the microstructure and sample composition during the fiber membrane construction process in detail. Figure 4 As shown in a, the D-PAN nanofibers are randomly distributed, with a smooth surface and a diameter of about 410 nm. The D-PAN@PDA core-shell structure fibers formed after polymerization in Tris-HCl solution still have a smooth surface and the diameter increases to about 600 nm ( Figure 4b), which solves the problem of uneven coating on the surface of nanofibers. The high-magnification SEM image of the fiber cross section clearly depicts the coaxial cable-like structure of D-PAN@PDA fibers ( Figure 4 c) The fiber is composed of a D-PAN core and an ultra-thick PDA shell. The PDA shell has a dense structure with a thickness of about 150 nm. Compared with before polymerization, the D-PAN fiber core not only has a smaller diameter, but also has a loose porous structure. This is mainly because during the induced polymerization process, as DA polymerizes on the surface of D-PAN nanofibers, the DA molecules inside the fiber continue to diffuse to the fiber surface, while PAN is insoluble in water and shows a tendency to gradually shrink inward, eventually resulting in an obvious cavity structure between the PDA shell and the D-PAN fiber core.

[0053] Example 4

[0054] The conjugated structure of PDA and water molecules and the relationship between donor and acceptor pairs were speculated.

[0055] Since the subsequent photothermal desalination experiment was carried out under wet conditions, exploring the relationship between PDA and water molecules may be the key to regulating the PDA absorption spectrum. Therefore, the density functional theory DFT method was used to theoretically calculate the possible donor-acceptor molecular conjugated structure of the PDA system at the B3LYP / 6-31G (d, p) level to understand the relationship between the structure of PDA and water molecules. We take the typical PDA dimer structure as an example, Figure 7 As shown in the figure, the calculated results of the LUMO / HOMO energy levels of the dimer before and after binding with water molecules are −0.45 eV / −4.64 eV and −0.55 eV / −4.63 eV, and their band gaps are 4.19 eV and 4.08 eV, respectively. According to the electron cloud distribution, after the PDA dimer binds to the water molecule, hydrogen bonding will be formed, which will improve the delocalization of electrons, reduce the PDA energy gap, and improve the light absorption capacity.

[0056] Example 5

[0057] The photothermal conversion ability, wettability and light absorption ability of the fiber membrane were tested.

[0058] In order to compare the photothermal effects of different fiber membranes, water and PAN fiber membrane were used as blanks to compare the photothermal heating performance of PAN@PDA fiber membrane, D-PAN@PDA fiber membrane and D-PAN@PDA@Ag fiber membrane. We dispersed the fiber membranes in water, respectively, and exposed them to vertical irradiation of 500 W cm-2 simulated sunlight while stirring, and recorded the temperature change of the system over time. Figure 5As shown in a, D-PAN@PDA@Ag fiber membrane showed the strongest photothermal effect. The temperature increased by 35 °C in 14 min, which was higher than the temperature increase of PAN fiber membrane, PAN@PDA fiber membrane, and D-PAN@PDA fiber membrane under the same conditions (increased by 18 °C, 20 °C, and 32 °C, respectively). The above results show that under simulated sunlight, the introduction of PDA makes the composite fiber membrane have a good photothermal effect, and the plasma photothermal effect of Ag nanoparticles further enhances the photothermal effect of the composite fiber membrane. The water contact angles of D-PAN, DPAN@PDA, and D-PAN@PDA@Ag fiber membranes were further tested. The results show that it takes 538 ms for a drop of water to spread completely on the surface of the D-PAN fiber membrane, while it only takes 173 ms and 175 ms to spread completely on the surface of the D-PAN@PDA fiber membrane and the D-PAN@PDA@Ag fiber membrane, indicating that the introduction of the PDA shell layer can improve the hydrophilicity of the fiber membrane, while the further loading of Ag nanoparticles has little effect on the hydrophilicity. Therefore, during the photothermal interface evaporation process, water can form an ultra-thin water film with a thickness of micrometers along the hydrophilic D-PAN@PDA@Ag nanocomposite photothermal fiber membrane, which, combined with the thermal insulation substrate, can achieve good thermal confinement and heat concentration effects. Good hydrophilicity not only helps the photothermal material to fully contact with water, but also promotes the rapid flow of water and the rapid diffusion of salt, keeping the photothermal evaporation surface clean. Next, the light absorption properties of D-PAN@PDA and D-PAN@PDA@Ag nanofiber membranes in the solar spectrum range of 200 nm to 2500 nm were compared. Figure 5 As shown in Figure c, by integrating the absorption peaks respectively, it can be obtained that the absorption rates of the D-PAN@PDA@Ag nanofiber membrane to the entire sunlight in dry and wet states are 78.9% and 88.6%, respectively, which are higher than the absorption rate of the PAN@PDA fiber membrane (70.3% in dry state and 76.0% in wet state). This is mainly because the Ag nanoparticles enhance the light absorption rate of the fiber membrane in the entire band, especially significantly enhance the absorption rate in the near-infrared band.

[0059] Example 6

[0060] Large-area preparation: Large-area D-PAN@PDA@Ag nanofiber membranes with excellent mechanical properties can be easily prepared by electrospinning and simple surface-induced in-situ polymerization. Due to the simplicity of the preparation method, this method can achieve large-area preparation of 30cm*30cm ( Figure 6 ).

[0061] Example 7

[0062] Testing the photothermal desalination capacity of photothermal membranes:

[0063] 1) Construct a solar thermal desalination device (such as Fig.10 ): The spatially separated seawater desalination device consists of bulk water at the bottom, insulating foam at the top, a cotton swab in the middle, and a photothermal fiber membrane covering the surface.

[0064] In order to evaluate the evaporation efficiency of the assembled photothermal evaporator, we tested its evaporation rate of simulated seawater under one-time solar illumination and compared the performance of different nanofiber membranes as photothermal conversion materials. Figure 8 As shown in a, under simulated sunlight, the interfacial water evaporation rate of the D-PAN@PDA@Ag film-based evaporator is the fastest, reaching 1.91 kg m-2 h-1. When cotton swab, PAN, PAN-Ag or D-PAN@PDA fiber membrane is used as the photothermal conversion material, the interfacial water evaporation rates are 0.34 kg m-2 h-1, 0.46 kg m-2 h-1, 0.94 kg m-2 h-1 and 1.48 kg m-2 h-1, respectively. The introduction of a thicker PDA shell layer not only improves light absorption, but also facilitates the in-situ generation of stable Ag nanoparticles. Compared with the PAN-Ag fiber membrane prepared by electrospinning photoreduction, the silver nanoparticles in the D-PAN@PDA@Ag fiber membrane are evenly distributed on the fiber surface, which is conducive to its effective absorption of sunlight, thereby obtaining a higher photothermal conversion efficiency. In order to further detect the evaporation surface temperature of the nanofiber membrane-based photothermal evaporator, a thermal infrared camera was used to test the temperature distribution of the evaporator under one-time illumination (1-sun) conditions, as shown in Figure 1. Figure 8 As shown in Figure b, the equilibrium temperatures of the evaporation surface and bulk water of the D-PAN@PDA@Ag nanofiber membrane-based evaporator are 34.2 °C and 20.6 °C, respectively, with a temperature difference of 13.6 °C. It can be seen that the spatial separation device can maintain a large temperature difference during the evaporation process, effectively reducing the diffusion of heat into the bulk water, promoting the concentration of heat and localizing it in the thin layer of water on the evaporation surface. Next, the evaporation rates under different light intensities are compared, as shown in Figure 2. Figure 8 As shown in c, the photothermal evaporation capabilities of D-PAN@PDA and D-PAN@PDA@Ag nanofiber membrane-based evaporators were tested under different light intensities. When the light intensity increased to 3 and 5 times the sunlight, the evaporation rates of the D-PAN@PDA@Ag nanofiber membrane evaporator were 5.32 kg m-2 h-1 and 8.19 kg m-2 h-1, while the evaporation rates of the D-PAN@PDA nanofiber membrane-based evaporator under 3 and 5 times the sunlight were 4.12 kg m-2 h-1 and 6.40 kg m-2 h-1 ( Fig. 9 ). Durability is one of the key properties of evaporators in practical applications, such as Figure 8As shown in Figure d, the D-PAN@PDA@Ag nanofiber membrane evaporator showed good evaporation stability in a continuous 12h cycle test, where each cycle lasted for 1 hour. The results showed that both D-PAN@PDA and D-PAN@PDA@Ag nanofiber membrane-based evaporators have good stable evaporation performance and strong practical application value. Photothermal evaporation efficiency is one of the key indicators for evaluating the evaporation performance of photothermal media and the photothermal interface of the evaporator. Formula 2-1 is used to calculate the photothermal energy conversion efficiency of the nanocomposite fiber membrane-based evaporator:

[0065] (1)

[0066] Where m is the water evaporation rate (minus the evaporation rate under dark conditions), H LV is the evaporation enthalpy of water, E in (kJ m - 2 h -1 ) is the incident light energy absorbed by the material. Formula 1 was chosen because the large number of functional groups on the PDA surface, which interact closely with water molecules, may affect the evaporation enthalpy of water on the material surface. This speculation was further confirmed by calculating the evaporation enthalpy of water on the surfaces of different materials (Table 1).

[0067] Table 1 Evaporation enthalpy of water on different fiber membrane surfaces in dark state △H

[0068]

[0069] The evaporation enthalpy of water is an important parameter in the evaporation process of water. By testing the evaporation rate of the evaporator under dark conditions, according to the law of conservation of energy, the evaporation enthalpy of water under dark conditions satisfies the formula, and the evaporation enthalpy of water on the surface of different materials during the evaporation process can be calculated. As can be seen from Table 1, compared with pure water, the evaporation enthalpy of water on the surface of the D-PAN@PDA and D-PAN@PDA@Ag nanofiber membrane-based evaporators with this spatial separation structure is greatly reduced, and the reduction in evaporation enthalpy is mainly attributed to the close intermolecular forces between the polyhydroxy / amino PDA polymer and the water molecules. By calculation, under 1 times the sunlight, the evaporation efficiency of the D-PAN@PDA@Ag nanofiber membrane evaporator is 85.5%, and even under 3 times and 5 times the sunlight, the evaporation efficiency can still reach 79.4% and 73.5%. The above results show that the D-PAN@PDA@Ag nanofiber membrane-based evaporator has a high photothermal evaporation rate and photothermal conversion efficiency, which is better than most of the reported spatial separation and PDA material evaporators ( Figure 8 e). In order to further evaluate the actual desalination performance of the D-PAN@PDA@Ag nanofiber membrane-based evaporator, the Na+ , K + , Ca 2+ and Mg 2+ The concentrations of four ions. Figure 8 As shown in (f), the concentrations of the four ions in the clean water collected after the simulated seawater was evaporated by the D-PAN@PDA@Ag nanofiber membrane-based evaporator were significantly reduced and met the drinking water standards of the World Health Organization (WHO), indicating that the D-PAN@PDA@Ag nanofiber membrane-based evaporator can be used for the production of actual drinking water.

[0070] The present invention prepares a D-PAN@PDA coaxial nanofiber membrane with an ultra-thick PDA shell layer by a simple layer-by-layer method, and in situ anchors Ag nanoparticles on the fiber surface to obtain a D-PAN@PDA@Ag photothermal nanocomposite fiber membrane with dual photothermal functions. The coating of the thicker PDA shell layer greatly improves the mechanical properties, chemical stability, light absorption rate and hydrophilicity of the photothermal fiber membrane. The stable Ag nanoparticles further improve the light absorption rate of the photothermal fiber membrane. The D-PAN@PDA@Ag photothermal nanocomposite fiber membrane is combined with a spatial separation evaporation device, and the prepared evaporator exhibits unique performance in the SDID system. The hydrophilic toughened nanocomposite fiber membrane has a large specific surface area, which is conducive to the continuous flow of water in the membrane, promotes the redispersion and reflux of salt to the bulk water, and improves the stability of the photothermal evaporator. In addition, the 40-micron-thick porous hydrophilic photothermal fiber membrane facilitates the rapid overflow of steam and makes the heated water layer distributed on the fiber membrane surface thinner. At the same time, the introduction of the space separation structure and the low thermal conductivity cotton swab is conducive to the heat concentration and thermal confinement of the nanofiber membrane-based evaporator, so that the evaporation rate of simulated seawater under 1 times the sunlight can reach 1.91 kg m-2 h-1, showing continuous and stable photothermal interface evaporation performance. The hydrogen bonding between PDA molecules and water was preliminarily explored through experimental analysis and density functional theory DFT calculations, which also provided new ideas for the construction and application expansion of photothermal fiber membrane materials, and has high practical value.

Claims

1. A method for preparing a Dx-PAN@PDA@Ag core-shell photothermal fiber membrane modified with an ultra-thick polydopamine layer, characterized in that: The Dx-PAN@PDA@Ag core-shell photothermal fiber membrane is composed of a polyacrylonitrile-dopamine fiber membrane and an ultra-thick polydopamine shell layer; the dopamine content in the polyacrylonitrile-dopamine fiber membrane is 0.1-3.00 mg / cm 2 ; The fiber diameter of the polyacrylonitrile-dopamine fiber membrane is 80-100nm; the thickness of the polydopamine shell layer is 400-600nm; after the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane is loaded with silver nanoparticles, the particle size of the silver nanoparticles is 20-30nm, and the loading amount of the silver nanoparticles is 1%-20%; The specific steps include: 1) Preparation of PAN-DA electrospinning solution: Dissolve DA in DMF, stir at room temperature, then add PAN, and continue stirring until all dissolved to obtain PAN-DA electrospinning solution, recorded as Dx-PAN spinning solution; 2) Preparation of electrospun Dx-PAN nanofiber membrane: The PAN-DA electrospinning solution was loaded into a syringe for electrospinning; after the spinning was completed, the electrospun membrane was removed and naturally dried for later use, which was recorded as the Dx-PAN nanofiber membrane; 3) Preparation of electrospun Dx-PAN@PDA core-shell photothermal fiber membrane with ultra-thick polydopamine layer: Take the prepared Dx-PAN nanofiber membrane, immerse it in Tris-HCl solution of DA, and stir it at room temperature; rinse the prepared membrane, vacuum dry it and set it aside, record it as Dx-PAN@PDA; 4) Preparation of electrospun Dx-PAN@PDA@Ag core-shell photothermal fiber membrane with ultra-thick polydopamine layer: Take the prepared Dx-PAN@PDA nanofiber membrane, immerse it in AgNO3 solution, let it stand for a period of time, rinse it with ultrapure water, and vacuum dry it to obtain Dx-PAN@PDA@Ag core-shell photothermal fiber membrane.

2. The preparation method according to claim 1, characterized in that: In step 1), the concentration of DA dissolved in DMF is 4-120 mg / mL; the stirring time is 1 hour; the molecular weight of PAN is between 80000 and 150000; the mass ratio of DA to PAN is 1:10 to 1:1; in the Dx-PAN, x is the content of DA, and the range of x is 0.1g~1.0g.

3. The preparation method according to claim 1, characterized in that: In step 2), the electrospinning parameters are as follows: the distance between the electrospinning needle and the receiving device is adjusted to 12-20 cm, the needle height is 35-45 cm, the injection speed is 0.01-0.1 mm / h, the voltage is 7-20 kV, the spinning needle moving distance is 20-100 cm, and the spinning time is 4-24 h.

4. The preparation method according to claim 1, characterized in that: In step 3), the concentration of DA in the Tris-HCl solution is 0.05-5 mg / mL; the Tris-HCl solution is a 0.1-0.6 wt % aqueous solution of tris(hydroxymethyl)aminomethane, the hydrochloric acid concentration is 0.1 M, and the pH of the solution is adjusted to 8.5; the stirring time at room temperature is 24 h; and the vacuum drying time is 12 h.

5. The preparation method according to claim 1, characterized in that: In step 4), the concentration of the AgNO3 solution is 1-100 mM; the standing time is 1-30 min; and the vacuum drying time is 12 h.

6. Application of the Dx-PAN@PDA@Ag core-shell photothermal fiber membrane prepared by the preparation method according to any one of claims 1 to 5 in photothermal desalination of seawater.

Citation Information

Patent Citations

  • Self-repairing nano fiber and preparation method and application thereof

    CN107829164A

  • Preparation method and application of polydopamine modified ZIF-8 functionalized nanofiber membrane

    CN109577005A